New Anticoagulants in the Treatment of VTE - Le Gal, Grégoire; Mottier, Dominique (Seminars in Respiratory and Critical Care Medicine, 2012)
Low molecular weight heparins (LMWHs) and vitamin K antagonists make up the cornerstone of therapy for patients with venous thromboembolism (VTE) but have drawbacks making their use difficult in daily practice. Current research focuses on the development of new anticoagulant drugs that could be administered orally at a fixed dose, with fewer food and drug interactions and no need for monitoring or dose adjustment. Several new drugs are tested in noninferiority trials, either as a single-drug approach treatment (e.g., rivaroxaban or apixaban), or after an initial course of LMWH (e.g., dabigatran or edoxaban). Published clinical trials demonstrate that rivaroxaban and dabigatran are noninferior to conventional treatment in patients with VTE. Several issues remain challenging for physicians, such as the lack of antidote and of routinely available monitoring tests. To what extent new anticoagulant drugs will change clinical practice is not yet well defined. They may facilitate outpatient management of VTE. They might also improve the risk–benefit balance of prolonged anticoagulation and therefore modify the optimal duration of anticoagulation in VTE patients.
Keywords: venous thromboembolism; anticoagulants; therapeutics; review